Viroconium
This base of a colonnade probably formed the front to one of the larger public buildings. It, too, is an echo of Imperial Rome where the Mediterranean climate led to the building of shaded spaces under which business could be conducted. Roman columns and the orders of architecture followed those of Greece, except that Roman materials were not so suitable for fluted columns and therefore, as in the examples here, were left circular in section.